Cross-Modal Analysis of Speech, Gestures, Gaze and Facial Expressions COST Action 2102 International Conference Prague, Czech Republic, October 15-18, 2008 Revised Selected and Invited Papers - Esposito, Anna; Vích, Robert (Lecture Notes in Artificial Intelligence, 2009)
This book constitutes the peer-reviewed post-conference proceedings of the Second COST Action 2102 International Conference on Cross-Modal Analysis of Speech, Gestures,Gaze and Facial Expressions held in Prague, Czech Republic during October 15-18, 2008. The 39 peer-reviewed papers presented are organized in three sections. The first section "Emotion and ICT," deals with themes related to the crossfertilization between studies on ICT practices of use and cross-modal analysis of verbal and nonverbal communication. The second section, "Verbal and Nonverbal Features of Computational Phonetics," presents original studies devoted to the modelling of verbal and nonverbal phonetics. The third section, "Algorithmic and Theoretical Analysis of Multimodal Interfaces," presents theoretical and practical implementations of original studies devoted to the analysis of speech, gestures, face and head movements as well as to learning issues in human-computer interaction and to algorithmic solutions for noise environments in human-machine exchanges.